Otoritas Alkitab dalam Era Postmodern - Budi Priyono; Arnold Tindas (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This article explores the challenges and opportunities faced by the authority of the Bible in the context of postmodern culture. Postmodernism—characterized by truth relativism, the deconstruction of meaning, and skepticism toward institutions—has significantly shifted society’s perception of authoritative texts, including Scripture. Drawing on key thinkers such as Lyotard, Derrida, Vanhoozer, and Grenz, the study examines how biblical authority is no longer universally accepted but interpreted through the lens of individual subjectivity and personal experience. In response to this shift, the article proposes several constructive hermeneutical approaches—contextual, narrative, communal, and pneumatological—that allow Christians to remain faithful to divine revelation while addressing the needs of contemporary culture. It also emphasizes the importance of embodied witness and the role of the church as a community of interpretation that brings the authority of the Bible to life in practical, relational, and socially relevant ways. Ultimately, this study concludes that although postmodernism questions claims of absolute truth, it also provides a meaningful space for the church to reimagine how Scripture can be lived out and communicated effectively in a changing world.